Evaluating the effects of diclofenac sodium and etodolac on renal hemodynamics with contrast-enhanced ultrasonography: a pilot study - Imamura, Hiroshi; Hata, Jiro; Iida, Ai; Manabe, Noriaki; Haruma, Ken (European journal of clinical pharmacology, 2013)
Purpose Contrast-enhanced ultrasonography (CEUS) is a novel approach used for measuring organ perfusion changes. Studies using CEUS to assess the effects of non-steroidal anti-inflammatory drugs (NSAIDs) on renal blood flow (RBF) have not yet been conducted. We aimed to evaluate the effects of NSAIDs on the renal hemodynamics of healthy subjects with CEUS. Methods We performed CEUS using the bolus injection method in a total of 10 healthy subjects. Measurements were completed over two study days in a randomized, crossover manner. On each study day, CEUS was performed twice, before and after the administration of NSAIDs. Subjects received an injection of contrast medium and images were recorded. A region-of-interest (ROI) was selected within the renal cortex, signal intensity in the ROI of the kidney was measured and a time-intensity curve (TIC) was automatically generated with attached software. Results The mean (±SD) peak intensity decreased significantly after an administration of diclofenac sodium (from 26.0 × 10 −4 ± 17.4 × 10 −4 AU to 19.2 × 10 −4 ± 12.0 × 10 −4 AU; P = 0.022), but not significantly with etodolac (from 26.5 × 10 −4 ± 9.7 × 10 −4 AU to 25.9 × 10 −4 ± 20.8 × 10 −4 AU; P = 0.474). The mean (±SD) percent reduction in intensity following diclofenac sodium administration was significantly reduced compared with etodolac administration (22.2 ± 20.5 % vs. 3.4 ± 8.9 %, P = 0.037). Conclusions These finding suggests that diclofenac sodium ( P = 0.022), but not etodolac ( P = 0.474), affects renal hemodynamics even in healthy subjects.